دراسة التعليم في الجزائر باستخدام نماذج بانيل - عدلي صليحة (جامعة الوادي University Of Eloued, 2024)
All the rapid changes and développements in the world imposed on the educational system in Algeria continuos changes in its composition, and this is so that it can achieve its goals in society, and the effectiveness of the educational system in Algeria is measured on the basis of exams and among the Most important exams is the Basic Education Certificate (BEM) And the baccalaureate certificate (BAC) and every state of the country has a percentage of benefiting from these achieved successes, but the percentage of each states contribution varies from one state to another, in addition to that the success rate is affected by factor and is subject to a spécifiques system and specificities, and for this we havestudied the success rates Using the MODEL PANELDATA.
A study of education in Algeria using Panel models
Keywords: Education; ، PanelModels; SOCIAL SCIENCES::Social sciences::Education; Teaching in Algeria; ‘Exams National in ALGERIAN